Luminescent Properties of a Water‐Soluble Conjugated Polymer Incorporating Graphene‐Oxide Quantum Dots. Issue 6 (4th February 2015) - Li, Penglei; Di Stasio, Francesco; Eda, Goki; Fenwick, Oliver; McDonnell, Shane O.; Anderson, Harry L.; Chhowalla, Manish; Cacialli, Franco
Abstract: We report the incorporation of graphene‐oxide quantum dots (GOQDs) into films, diluted solutions, and light‐emitting diodes (LEDs) as part of a water‐soluble derivative of poly( p ‐phenylene vinylene), or PDV.Li, to investigate their impact on the light‐emission properties of this model conjugated polymer. Despite the well‐known ability of graphene and graphene oxide to quench the photoluminescence of nearby emitters, we find that the addition of GOQDs to diluted solutions of PDV.Li does not significantly affect the photoluminescence (PL) dynamics of PDV.Li, bringing about only a modest quenching of the PL. However, loading the polymer with GOQDs led to a substantial decrease in the turn‐on voltage of LEDs based on GOQD–PDV.Li composites. This effect can be attributed to either the improved morphology of the host polymer, resulting in an increase in the charge mobility, or the enhanced injection through GOQDs near the electrodes. Abstract : Strange but true: Small quantities of graphene‐oxide quantum dots blended in the active layer of polymer light‐emitting diodes boost the current density by reducing the turn‐on voltage; yet, unexpectedly, they do not decrease the photoluminescence efficiency of the active layer.